2016
DOI: 10.1002/pds.3986
|View full text |Cite
|
Sign up to set email alerts
|

Drug use among men with unfulfilled wish to father children: a retrospective analysis and discussion of specific drug classes

Abstract: A high percentage of involuntarily childless men is taking drugs that can potentially influence male reproductive function. As drug intake represents a modifiable risk factor, fertility evaluation requires a comprehensive medication review including prescription and non-prescription drugs. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…13 It has been estimated that among involuntary childless men that present to infertility clinics, 25% take drugs that have the potential to negatively impact male sexual function and 10% take drugs associated with male fertility impairment. 42 Furthermore, several psychosocial factors, associated with a diagnosis of IA, may have contributed to the lower fertility rate as observed in this study. 43 In our study, due to problems or concerns associated with IA and its treatment and based on medical advice (or the lack of), men with IA and their partners decided to become voluntarily childless or to delay their plans to become parents.…”
Section: Inflammatory Arthritismentioning
confidence: 65%
See 1 more Smart Citation
“…13 It has been estimated that among involuntary childless men that present to infertility clinics, 25% take drugs that have the potential to negatively impact male sexual function and 10% take drugs associated with male fertility impairment. 42 Furthermore, several psychosocial factors, associated with a diagnosis of IA, may have contributed to the lower fertility rate as observed in this study. 43 In our study, due to problems or concerns associated with IA and its treatment and based on medical advice (or the lack of), men with IA and their partners decided to become voluntarily childless or to delay their plans to become parents.…”
Section: Inflammatory Arthritismentioning
confidence: 65%
“… 13 It has been estimated that among involuntary childless men that present to infertility clinics, 25% take drugs that have the potential to negatively impact male sexual function and 10% take drugs associated with male fertility impairment. 42 …”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that apart from conventional male reproductive toxicity assessment by measuring the weight of reproductive organs such as testis, epididymis and prostate, analysis of sperm motility and viability, macroscopic and histological examination and changes in hormone levels [7,8] , the protein profi le can also be used to evaluate the male reproductive toxicity [9][10][11][12] . The present study was aimed to evaluate the alterations in the sperm count, ion concentration and pattern of protein profi le in cauda and caput after treatment with VCR thus leading to compromised epididymal functions.…”
Section: Research Papermentioning
confidence: 99%
“…Indeed, the impact of drugs on male fertility is rather neglected. For instance, in a retrospective study, 47% of men with an unfulfilled wish to father a child took drugs, with 16% of those with a known fertility impairment and 51% with an impairment of male sexual function [ 35 ].…”
Section: Discussionmentioning
confidence: 99%